2007
DOI: 10.1021/es0629054
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Involved in the Evolution of Physically Irreversible Fouling in Microfiltration and Ultrafiltration Membranes Used for Drinking Water Treatment

Abstract: Control of membrane fouling is important for more efficient use of membranes in water treatment. Control of physically irreversible fouling, which is defined as fouling that requires chemical cleaning to be cancelled, is particularly important for reduction of operation cost in a membrane process. In this study, a long-term filtration experiment using three different types of MF and UF membranes was carried out at an existing water purification plant, and the evolution of physically irreversible fouling was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
81
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(88 citation statements)
references
References 25 publications
7
81
0
Order By: Relevance
“…Internal fouling arises from the adsorption of organic matters that are smaller than the membrane pore size leading to the pore narrowing [16]. To determine internal fouling and its effect on hydraulically irreversible fouling, additional fouling experiments were carried out with the permeate water of the individual membranes.…”
Section: Fouling Experiments With Permeate Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Internal fouling arises from the adsorption of organic matters that are smaller than the membrane pore size leading to the pore narrowing [16]. To determine internal fouling and its effect on hydraulically irreversible fouling, additional fouling experiments were carried out with the permeate water of the individual membranes.…”
Section: Fouling Experiments With Permeate Watermentioning
confidence: 99%
“…Humic substances [10][11][12][13][14] and biopolymers [15][16][17][18][19][20][21] in natural surface water have been intensively acknowledged as the main organic foulants on UF/MF membranes in both hydraulically reversible and irreversible fouling. Zheng et al [22] identified organic matter larger than the UF pore size as the major foulants, which contribute to the cake layer formation, while only a small remaining portion (unquantified) remains as hydraulically irreversible fouling after backwash.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that humic substances caused severe irreversible fouling due to adsorption, while alginate should have a most detrimental effect on membrane fouling, but mostly reversible. Through investigating the fouling behavior of natural water in three different types of MF and UF membranes, Yamamura et al [12] revealed that carbohydrates were dominant in the membrane foulants regardless of the types of membranes. Other researchers [13,14] considered that a high content of hydrophilic fraction or hydrophilic neutral fraction in the nature water caused serious flux decline, by using hydrophobic and hydrophilic MF and UF membranes on the NOM isolated from different surface water.…”
Section: Introductionmentioning
confidence: 99%
“…16) To achieve reliable membrane performance, the fouled membranes should be periodically recovered using hydraulic back-washing (for reversible fouling) or chemical cleaning (for irreversible fouling). 17) Even though other methods (such as pretreatment of the feed and optimization of the operating conditions) are available for membrane maintenance, they do not provide satisfactory results because of the increased operation cost and decreased membrane lifetime. 18) Thus, surface modification is becoming a critical technique for the development of novel ceramic membranes with excellent fouling resistance.…”
Section: Introductionmentioning
confidence: 99%